EFFECTIVE APPROACHES TO IMPROVING READING AND WRITING SKILLS IN ENGLISH LANGUAGE TEACHING - Gasimzada Aysel, (Research Focus International Scientific Journal, 2025)
Improving reading and writing skills in English language teaching is the foundation of success for language learners. These skills have a great impact not only on academic results, but also on the development of communication in every area of ​​daily life. For example, reading skills improve students' ability to understand and extract relevant information from a variety of texts, which gives them better analytical and critical thinking skills. At the same time, writing skills allow students to express their thoughts and ideas correctly, clearly and logically. It plays an important role not only for written assignments but also in communication in everyday life, as a well-written letter, e-mail or report is essential for conveying the right information. Also, reading and writing skills not only improve language learners' general language skills, but also strengthen their motivation towards the language.